The concept of the restoration project of the Hryhorii Skovoroda museum in the context of preserving Ukrainian cultural heritage objects - Severyn, Viktor; Severyn, Nadiia (Kyiv National University of Culture and Arts, 2024)
The aim of the article is to present the concept of the project decision regarding the restoration of the Hryhorii Skovoroda Museum taking into account the preservation of objects of Ukrainian cultural heritage. Results. The foreign and domestic experience of preserving cultural heritage in the context of the world culture, which forms the basis of the elaborated project, is analysed. The development strategy and the main reconstruction goals of the Hryhorii Skovoroda Museum are determined. In the architectural and planning decision, it is aimed to use such compositional techniques as symmetry and geometry. It is mentioned that the forming elements of design are created on the basis of images associated with the life of H. S. Skovoroda or heroes of his creative works. Measures for restorating garden and park ensemble and the restoration project of H. S. Skovoroda’s museum as an object of cultural heritage of national signifiance are offered. Scientifi novelty. The concept of the mentioned project offers directions for restorating the Hryhorii Skovoroda Museum that meet modern requirements for creating museum exhibits with mandatory consideration of universal design (inclusive design), aimed at meeting such requirements as accessibility, safety, informativeness, convenience, environment comfort for all people, particularly with various health disabilities (physical, psychological, etc.), and of different age category. Conclusions. The museum’s development strategy involves spreading knowledge about Hryhorii Skovoroda, attracting a wide range of the museum visitors, ensuring the full functioning of the museum as a scientifi, cultural and educational institution, its further development as a centre of cultural and artistic life. Involvement of architectors and environment designers can allow to create a project offer for the new building and museum interiors, taking into account the preserved exhibition objects. Functionality and ergonomics of this museum areas are planned in such a way that people with disabilities can have an opportunity to visit the exhibition without any obstacles. An important element in the development of interior design is lighting and usage of elements with the modern technologies. Therefore, the creation of a museum exposition is a complex task, which can be realised due to the synthesis of the designer’s creative ideas, the system of images, objects, events, phenomena and innovative interactive technologies, which create a complete picture, such as an exhibition image.

Мета статті — представити концепцію проєктного рішення щодо відновлення Національного літературно-меморіального музею Г. С. Сковороди з урахуванням особливостей збереження об’єктів культурної спадщини України. Результати дослідження. Проаналізовано зарубіжний і вітчизняний досвід збереження культурної спадщини в контексті світової культури, що становить основу розробленого проєкту. Визначено стратегію розвитку музею Григорія Сковороди та основні цілі його відбудови. В архітектурно-планувальному рішенні заплановано використати такі композиційні засоби, як симетрія та геометричність. Зазначено, що формоутворювальні елементи дизайну створені на основі образів, які пов’язані з життям Г. С. Сковороди чи героями його творів. Запропоновано заходи з відновлення садово-паркового ансамблю та проєкт відновлення музею Г. С. Сковороди як об’єкта культурної спадщини національного значення. Наукова новизна. Концепція зазначеного проєкту пропонує напрями відновлення Національного літературно-меморіального музею Г. С. Сковороди, які відповідають сучасним вимогам до створення музейних експозицій з обов’язковим урахуванням універсального (інклюзивного) дизайну, спрямованого на дотримання таких вимог, як доступність, безпека, інформативність, зручність, комфортність середовища для всіх людей, зокрема з різними вадами здоров’я (фізичними, психологічними тощо), та різної вікової категорії. Висновки. Стратегія розвитку музею передбачає поширення знань про Григорія Сковороду, залучення до музею широкого загалу відвідувачів, забезпечення повноцінного функціонування музею як наукового та культурно-просвітницького закладу, подальший його розвиток як осередку культурно-мистецького життя. Залучення архітекторів і дизайнерів середовища дозволить створити проєктну пропозицію щодо нової будівлі та інтер’єрів музею з урахуванням збережених експозиційних предметів. Функціональність та ергономічність музейних зон планується так, щоб люди з обмеженими можливостями могли безперешкодно відвідувати експозицію. Важливим елементом дизайну інтер’єру є освітлення та застосування елементів з новітніми технологіями. Отже, створення музейної експозиції - це складне завдання, яке реалізується завдяки синтезу творчого задуму дизайнера, системи образів, предметів, подій, явищ і сучасних інтерактивних технологій, які разом створюють цілісну картину — експозиційний образ.
Концепція проєкту відновлення Національного літературно-меморіального музею Г. С. Сковороди в контексті збереження об'єктів культурної спадщини України
Keywords: cultural heritage; place of memory; Slobozhanshchyna; design of museum expositions; architecture and landscape design; the Hryhorii Skovoroda Museum; культурна спадщина; місце пам'яті; Слобожанщина; дизайн музейних експозицій; архітектурно-ландшафтний дизайн; Національний літературно-меморіальний музей Г. С. Сковороди